Ultrafast Assembly of PS‐PDMS Block Copolymers on 300 mm Wafers by Blending with Plasticizers. (7th June 2016) - Arias‐Zapata, Javier; Böhme, Sophie; Garnier, Jérôme; Girardot, Cécile; Legrain, Antoine; Zelsmann, Marc
Abstract : Next‐generation lithography techniques based on the self‐assembly of block copolymers (BCPs) are promising methods for high‐resolution pattering. BCPs with a high incompatibility (high‐χ), such as polystyrene‐polydimethylsiloxane (PS‐PDMS), show encouraging results in terms of resolution. In the strong segregation regime, the high diffusive energy barrier of PS‐PDMS excessively reduces the self‐assembly kinetics; this is why solvent–vapor annealing is typically adopted to shorten the self‐assembly time. Plasticizers are generally used to reduce the glass transition temperature ( T g ) of polymers. In this study, commercial plasticizers such as dioctylsebacate and diisooctyl adipate are blended with PS‐PDMS polymers, and their influence on the self‐assembly process is investigated. The intrinsic PS selectivity of the plasticizers brings the BCP to form PS‐PDMS micelles, which results in highly ordered self‐assembled body‐centered cubic spherical PS‐PDMS after spin‐coating without any annealing. The negligible vapor pressure of plasticizers and the decrease of T g allow the high mobility of PS‐PDMS micelles in thin films. A transition into a stable horizontal cylindrical morphology is then possible by ultrafast thermal annealing (30 s). The complete process, from the BCP deposition to the final pattern transfer into Si, is presented on 300 mm standard wafers, which makes this method promising for microelectronic industrial integration. Abstract : High‐χN PS‐PDMS block copolymers are blended with plasticizers in order to trigger self‐assembly. The plasticizers allow high mobility of PS‐PDMS micelles, which leads to homogeneous self‐assembled structures after deposition and a well‐aligned morphology transition by 30 s thermal annealing. The process has been tested on 300 mm wafers of standard graphoepitaxy trenches, and pattern transfer into Si substrates has been successfully performed.